Mechanical Thrombectomy for Acute Stroke - Versnick, Eric J.; Do, Huy M.; Albers, Greg W.; Tong, David C.; Marks, Michael P. (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: We evaluated a mechanical thrombectomy protocol to treat acute stroke and report the angiographic results and clinical outcomes.METHODS: Patients with anterior circulation strokes <8 hours and posterior circulation strokes <12 hours were treated at a single center over 10 months. Patients were excluded if they were candidates for intravenous tissue plasminogen activator (tPA). Treatment involved one of two mechanical thrombectomy devices. Retrieval was augmented by low-dose intra-arterial tPA if needed. Outcome was measured by using the Modified Rankin score.RESULTS: Ten patients were treated: five with anterior circulation strokes, four with posterior circulation strokes, and one with embolic strokes involving both circulations. Mean National Institutes of Health Stroke Scale score at presentation was 24.6 ± 10.9. In eight patients (80%), revascularization was successful (Thrombolysis in Acute Myocardial Infarction score, 3). Mean time from symptom onset to initiation of the procedure was 6 hours (5.3 hours for anterior circulation and 7.0 hours for posterior circulation). Mean time for recanalization from the start of the procedure was 1.17 ± 0.58 hours for the six anterior circulation strokes and 2.75 ± 1.34 hours in the two posterior circulation strokes. Five patients died within 48 hours; all had posterior circulation strokes. Mean Modified Rankin score at 90 days was 1.4.CONCLUSION: In this small series, mechanical thrombectomy of acute stroke appeared to improve recanalization rates compared with intra-arterial thrombolysis. No hemorrhagic complications occurred. Further study is required to determine the role of these techniques.